Group portrait of the attendees of the 1st United Methodists Youth Conference in Oakland, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 1st United Methodists Youth Conference, held Spetember 1-4, 1939 at the First Methodist Church in Oakland, California.